ElasticSearch cookbook : over 130 advanced recipes to search, analyze, deploy, manage, and monitor data effectively with ElasticSearch - Paro, Alberto (Quick answers to common problems., 2015)
If you are a developer who implements ElasticSearch in your web applications and want to sharpen your understanding of the core elements and applications, this is the book for you. It is assumed that you've got working knowledge of JSON and, if you want to extend ElasticSearch, of Java and related technologies.